Baseline Serum C-Reactive Protein and Plasma Fibrinogen-Based Score in the Prediction of Survival in Glioblastoma - Wach, Johannes; Apallas, Stefanos; Schneider, Matthias; Güresir, Agi; Schuss, Patrick; Herrlinger, Ulrich; Vatter, Hartmut; Güresir, Erdem (Frontiers in Oncology, 2021)
Objective: The present study investigates a score based on baseline C-reactive protein (CRP) and fibrinogen values (FC score) in 173 consecutive glioblastoma (GB) patients. Methods: The optimal cut-off value for fibrinogen and CRP was defined as 3.5 g/dl and 3.0 mg/L, respectively, according to previous reports. Patients with elevated CRP and fibrinogen were classified with a score of 2, those with an elevation of only one of these parameters were allocated a score of 1, and those without any abnormalities were assigned a score of 0. Results: No significant differences in age, gender, tumor area, molecular pathology, physical status, or extent of resection were identified among the three groups defined by this score. Univariate survival analysis demonstrated that a high baseline FC score (≥1) is significantly associated with a shortened overall survival (OS) (HR:1.52, 95%CI:1.05–2.20,p=0.027). A multivariate Cox regression analysis considering age (>65/≤65), extent of resection (GTR/STR), MGMT promoter status (hypermethylated/non-hypermethylated), and FC score (0/≥1) confirmed that an elevated FC score (≥1) is an independent predictor of shortened OS (HR:1.71, 95%CI:1.16-2.51,p=0.006). Conclusions: The baseline fibrinogen and CRP score thus serves as an independent predictor of OS in GB. Further investigations of the role of inflammation in the prediction of a prognosis are needed.